Highly Luminescent, Size- and Shape-Tunable Copper Indium Selenide Based Colloidal Nanocrystals - Yarema, Olesya; Bozyigit, Deniz; Rousseau, Ian; Nowack, Lea; Yarema, Maksym; Heiß, Wolfgang; Wood, Vanessa (Chemistry of Materials, 2013)
We report a simple, high-yield colloidal synthesis of copper indium selenide nanocrystals (CISe NCs) based on a silylamide-promoted approach. The silylamide anions increase the nucleation rate, which results in small-sized NCs exhibiting high luminescence and constant NC stoichiometry and crystal structure regardless of the NC size and shape. In particular, by systematically varying synthesis time and temperature, we show that the size of the CISe NCs can be precisely controlled to be between 2.7 and 7.9 nm with size distributions down to 9-10%. By introducing a specific concentration of silylamide-anions in the reaction mixture, the shape of CISe NCs can be preselected to be either spherical or tetrahedral. Optical properties of these CISe NCs span from the visible to near-infrared region with peak luminescence wavelengths of 700 to 1200 nm. The luminescence efficiency improves from 10 to 15% to record values of 50-60% by overcoating as-prepared CISe NCs with ZnSe or ZnS shells, highlighting their potential for applications such as biolabeling and solid state lighting.
Keywords: copper indium selenide; CISe nanocrystals; size and shape control; quantum dot colloids; luminescence; lighting applications